2012
DOI: 10.1111/bjep.12000
|View full text |Cite
|
Sign up to set email alerts
|

The relation between school entrance age and school achievement during primary schooling: Evidence from Croatian primary schools

Abstract: Students who are older when they enter school perform slightly better than their older classmates in the lower grades of primary school, but these differences in achievement are very small and are probably no longer present by the end of primary schooling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 50 publications
1
18
0
1
Order By: Relevance
“…Araştırmalarda (Elder & Lubotsky, 2009;Sakic, Burusic, & Babarovic, 2013;Stipek, 2002) genellikle okula daha büyük yaşta başlayan çocukların okul yaşamında daha iyi performans gösterdiği iddia edilmektedir. Sakic ve arkadaşları (2013) tarafından 4. sınıf öğrencileri arasında yapılan çalışmada okula başlama yaşına göre akademik başarı açısından farklılıklar ortaya konmuştur.…”
Section: Okula Başlama Yaşı Ile Akademik Başarı Arasındaki İlişkiunclassified
“…Araştırmalarda (Elder & Lubotsky, 2009;Sakic, Burusic, & Babarovic, 2013;Stipek, 2002) genellikle okula daha büyük yaşta başlayan çocukların okul yaşamında daha iyi performans gösterdiği iddia edilmektedir. Sakic ve arkadaşları (2013) tarafından 4. sınıf öğrencileri arasında yapılan çalışmada okula başlama yaşına göre akademik başarı açısından farklılıklar ortaya konmuştur.…”
Section: Okula Başlama Yaşı Ile Akademik Başarı Arasındaki İlişkiunclassified
“…To maintain indoor thermal comfort in a region with fluctuating temperatures, household natural ventilation changes with the seasons. Several studies have investigated associations of birth month or season with learning capacity and intelligence quotient (IQ) level in childhood and adolescence . Associations were statistically significant in most studies and seemingly implied that early life household ventilation, especially as it changes with indoor‐outdoor temperature variation, may be related to learning capacity in childhood and adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated associations of birth month or season with learning capacity and intelligence quotient (IQ) level in childhood and adolescence. [14][15][16][17][18][19][20][21][22][23][24][25][26] Associations were statistically significant in most studies and seemingly implied that early life household ventilation, especially as it changes with indoor-outdoor temperature variation, may be related to learning capacity in childhood and adolescence. However, the findings in such studies have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this study was to determine if the change in SEA law created significantly better outcomes for students when assessed using the BKS. Sakic et al (2012) suggested a closer look at SEA by using a child's actual birthdate to determine differences in readiness. In my study, I responded to this call for further research by investigating the relationship between SEA (based on the student's exact age) and school readiness in a large urban district.…”
Section: Chapter V: Discussionmentioning
confidence: 99%
“…The context of my study was JCPS, a large urban district in the Commonwealth of Kentucky. I examined a new set of data in Jefferson County because legislation changed school entry age requirements effective the 2017-2018 school year.Data was gathered through the research and evaluation office within JCPS Sakic et al (2012). suggest a closer look at school entry age (SEA) by using a child's actual birthdate to determine differences in readiness.…”
mentioning
confidence: 99%